Juvenile Idiopathic Arthritis Associated Uveitis. Modern Therapy Approaches: Narrative Review - Alexandr A. Yakovlev; Tatiana N. Nikitina; Mikhail M. Kostik (Вопросы современной педиатрии)
Juvenile idiopathic arthritis (JIA) associated uveitis is the most common extra-articular manifestation of JIA. Nowadays, unified approach for the management of this condition has been developed despite all the difficulties in diagnosis. It allows to avoid many long-term complications and improves patients’ quality of life. Rapid development of pharmacotherapy (including appearance of new immunosuppressive and genetically engineered biologic drugs) expands the therapeutic methods and increases the chances in achieving sustained remission. However, still there are many questions regarding genetically engineered biologic drugs safety, optimal time to treatment cessation, and long-term follow-up in patients with JIA. This review summarizes and analyzes modern data regarding treatment approaches, therapy efficacy and safety, and perspectives for managing patients with uveitis and JIA.